Highly chemo- and regioselective C–P cross-coupling reaction of quinone imine ketals with Ar2P(O)H to construct ortho-amino triarylphosphine derivatives. Issue 13 (8th May 2019) - Liu, Teng; Li, Yongqin; Cheng, Feixiang; Shen, Xianfu; Liu, Jianjun; Lin, Jun
Abstract : The first highly selective C–P cross-coupling reaction of QIKs with Ar2 P(O)H to construct ortho -amino triarylphosphine derivatives has been developed. Furthermore, a series of functionalized organophosphorus were accomplished. Abstract : A highly chemo- and regioselective approach for the construction of ortho -amino triarylphosphine oxides has been achieved through a C–P cross-coupling reaction involving quinone imine ketals (QIKs) with Ar2 P(O)H and catalyzed via a Lewis base. This alternative protocol provided a wide substrate scope with excellent yields (82–95%), and a variety of ortho -amino triarylphosphines were obtained with high yields (87–95%) via further reductive reaction. Furthermore, this reaction could be scaled-up and several synthetic transformations were accomplished for the construction of functionalized organophosphorus.